Petrology of the Ispendere (Malatya) ophiolite from the Southeast Anatolia: implications for the Late Mesozoic evolution of the southern Neotethyan Ocean - Parlak, Osman; Karaoglan, Fatih; Rizaoglu, Tamer; Nurlu, Nusret; Bagci, Utku; Hock, Volker; Topak, Yusuf (Geological Soc Publishing House, 2013)
The Ispendere ophiolite forms part of the Tauride active continental margin assemblage in SE Anatolia. The ophiolite exhibits an intact oceanic lithosphere section and is intruded by Late Cretaceous calc-alkaline granites. The ophiolite comprises mantle tectonites, ultramafic to mafic cumulates, isotropic gabbros, isolated diabase dykes, a sheeted dyke complex, plagiogranite and volcanic rocks. The volcanics and the sheeted dyke complex exhibit (1) similar rare earth element patterns, with flat to light rare earth element depletion (La-Yb)(N) = 0.71-1.14 and 0.65-1.22, (2) negative Nb anomalies and (3) flat-lying high field strength element trends. These features differ from a typical Normal-Mid Ocean Ridge Basalt fractionation trend and could have resulted from c. 15% partial melting of a previously depleted mantle source. The whole-rock chemistry and the mineral chemistry of the ultramafic to mafic cumulates [high Ca plagioclases (An(89-81)), magnesian olivines (Fo(88-81)) and clinopyroxenes (Mg#(90-83))] show that the primary magma of the plutonic suite is compositionally similar to modern island arc tholeiites. The available evidence suggests that the Ispendere ophiolite formed at a northerly supra-subduction zone spreading centre of the Southern Neotethys, between the Taurides and the Bitlis-Puturge metamorphic units, during the Late Cretaceous. Comparison with the adjacent Goksun, Komurhan and Guleman ophiolites suggests that the Ispendere ophiolite represents part of a single regional-scale sheet of oceanic lithosphere that was accreted to the base of Tauride active continental margin where it was cut by arc-type magmatic rocks.
7th International Symposium on Eastern Mediterranean Geology -- OCT 18-22, 2010 -- Adana, TURKEY
Keywords: Calc-Alkaline Differentiation; Pozanti-Karsanti Ophiolite; Diverse Magma Generations; Kizildag Hatay Ophiolite; Island-Arc; Mineral Chemistry; Volcanic-Rocks; Baer-Bassit; Fore-Arc; Fractional Crystallization